Efectiveness of Shallot Root Extract Local Palu Against Candida albicans Fungus and its Utiliation as Learning Media - Mirfadz Maharani; I Nengah Kundera; I Made Budiarsa (Equator Science Journal, 2025)
The potential of Palu local shallot roots as an antifungal agent has not been optimally utilized. The aim of this research is to determine the effectiveness of Palu local shallot root extract against the fungus Candida albicans, identify the optimal concentration for inhibiting the growth of Candida albicans, and to use the findings as an educational medium. This research employed a laboratory experimental method with a completely randomized design (CRD) consisting of 5 treatments and 4 replications at concentrations of 0% as a negative control, 25%, 50%, 75%, and 100%. The Candida albicans fungus was obtained from Paramartha Lab Mojokerto with strain code ATCC-14053. The parameter observed was the diameter of the inhibition zone formed. The data were analyzed using Analysis of Variance (ANOVA), followed by a Least Significant Difference (LSD) test. The results of this study showed that the extract of Palu local shallot roots effectively inhibited the growth of Candida albicans* at a concentration of 100%. This research is feasible to be used as an educational medium in the form of a digital flipbook with an eligibility percentage of 87.08%.